Blood Storage Conditions Affect Hematological Analysis in Samples From Healthy Donkeys and Donkeys With Experimentally-Induced Endotoxemia - Perez-Ecija, Alejandro; Buzon-Cuevas, Antonio; Aguilera-Aguilera, Raul; Gonzalez-De Cara, Carlos A.; Mendoza, Francisco J. (Frontiers in Veterinary Science, 2020)
Preanalytical factors such as storage time and temperature are proved to induce marked artifactual changes in hematological parameters in horses, small animals and humans. These errors can mirror findings typical of endotoxemia, leading to dangerous misdiagnosis. Since donkeys are common in warm climates and remote regions, blood samples from this species can be subjected to long lasting travels from the farm to the nearest laboratory, frequently under suboptimal conditions. Moreover, as other equids, donkeys are prone to suffer endotoxemia. Nonetheless, stability has not been evaluated in samples for hematology in this species. The aim of this study was to characterize the effect of temperature and storage time in hematological parameters from healthy donkeys and donkeys with induced endotoxemia. Blood samples were collected from 6 healthy female Andalusian donkeys and stored for 6, 12, 24 and 48 h at several temperatures (4, 24 and 35 ºC). Endotoxemia was induced in the same animals by an intravenous LPS infusion and samples obtained 30 minutes post-infusion were handled similarly. Hematological analysis was performed using a laser-based analyzer and blood smear examination. Storage at 24 ºC caused significant neutropenia after 48 h as well as morphological changes typical of endotoxemia in blood from healthy donkeys as soon as 24 h post-storage. Samples kept at 35 ºC displayed more profound and earlier artifactual variations. Conservation at 4 ºC did not cause any significant change in blood parameters. Prolonged (48 h) storage of samples from animals with induced endotoxemia at 24 and 35 ºC accentuated pre-existing leukopenia and neutropenia. These findings highlight that donkey samples should be stored at 4 ºC, instead of 24 ºC as recommended for horses. Moreover, blood smear interpretation should be cautious in samples stored for longer than 24 hours and could be misleading when blood is kept at 35 ºC.